Research progress on the mechanism of radiation enteritis - Fan, Jinjia; Lin, Binwei; Fan, Mi; Niu, Tintin; Gao, Feng; Tan, Bangxian; Du, Xiaobo (Frontiers in Oncology, 2022)
Radiation enteritis（Re）is one of the most common complications of radiation therapy for Abdominal tumors. The efficacy of cancer treatment by radiation is often limited by the side effects of Re. Re can be acute or chronic. Treatment of acute Re is essentially symptomatic. However, chronic Re usually requires surgical procedures. The mechanisms underpinning Re are complex and have not yet been elucidated. The purpose of this review is to provide an overview of the pathogenesis of Re in the recent literature, including intestinal epithelial cells, intestinal stem cells, vascular endothelial cell, and intestinal microflora, etc. And it points the way to better treatment of Re.